"It's not just parties, it's so much more": student perceptions of the credibility of UK events management degrees. Issue 1 (4th November 2021) - Fletcher, Thomas; Ormerod, Neil; Dashper, Katherine; Musgrave, James; Bradley, Andrew; Marvell, Alan
Abstract : Purpose: This article explores (1) student perceptions and understanding of Events Management; (2) how Events Management is positioned by different UK Higher Education providers through their online marketing; and (3) the perceived value of an Events Management degree among students. Design/methodology/approach: A mixed-methods approach, combining an online student questionnaire ( n = 524), semi-structured interviews with current first year Events Management students ( n = 24) at two UK universities, and website analysis of all Events Management degrees offered in the UK. Findings: Students demonstrate a lack of knowledge about what Events Management is, what a career in Events Management might entail and the perceived value of an Events Management degree. This suggests the need to reposition Events Management degrees within a broader applied management base. Current course marketing presents a narrow view of Events Management degrees and the narrow vocationally-laden narrative undersells and "over-vocationalises" the subject. Practical implications: Understanding student perceptions better will help universities market Events Management degrees more effectively and will benefit broader efforts to illustrate the value and credibility of it as a degree subject choice and career. More balanced presentation between the practical and non-practical aspects of the courses in university marketing may help reposition Events Management alongside more readily understood vocational subjects. Originality/value: This is the first study to examine student perceptions over the credibility of Events Management degrees. It also addresses Park and Park's (2017) observation that reviews of Events Management education and curricula are conspicuously absent from Hospitality and Tourism journals.